Risk of survival, establishment and spread of Batrachochytrium salamandrivorans (Bsal) in the EU. (30th April 2018) - ,; More, Simon; Angel Miranda, Miguel; Bicout, Dominique; Bøtner, Anette; Butterworth, Andrew; Calistri, Paolo; Depner, Klaus; Edwards, Sandra; Garin‐Bastuji, Bruno; Good, Margaret; Michel, Virginie; et al.
Abstract: Batrachochytrium salamandrivorans (Bsal) is an emerging fungal pathogen of salamanders. Despite limited surveillance, Bsal was detected in kept salamanders populations in Belgium, Germany, Spain, the Netherlands and the United Kingdom, and in wild populations in some regions of Belgium, Germany and the Netherlands. According to niche modelling, at least part of the distribution range of every salamander species in Europe overlaps with the climate conditions predicted to be suitable for Bsal. Passive surveillance is considered the most suitable approach for detection of Bsal emergence in wild populations. Demonstration of Bsal absence is considered feasible only in closed populations of kept susceptible species. In the wild, Bsal can spread by both active (e.g. salamanders, anurans) and passive (e.g. birds, water) carriers; it is most likely maintained/spread in infected areas by contacts of salamanders or by interactions with anurans, whereas human activities most likely cause Bsal entry into new areas and populations. In kept amphibians, Bsal contamination via live silent carriers (wild birds and anurans) is considered extremely unlikely. The risk‐mitigation measures that were considered the most feasible and effective: (i) for ensuring safer international or intra‐EU trade of live salamanders, are: ban or restrictions on salamander imports, hygiene procedures and good practice manuals; (ii) for protecting kept salamanders from Bsal, are: identification and treatment of positive collections; (iii) for on‐site protection of wild salamanders, are: preventing translocation of wild amphibians and release/return to the wild of kept/temporarily housed wild salamanders, and setting up contact points/emergency teams for passive surveillance. Combining several risk‐mitigation measures improve the overall effectiveness. It is recommended to: introduce a harmonised protocol for Bsal detection throughout the EU; improve data acquisition on salamander abundance and distribution; enhance passive surveillance activities; increase public and professionals' awareness; condition any movement of captive salamanders on Bsal known health status.